Evaluation of pH, Calcium Ion Release, and Dimensional Stability of an Experimental Silver Nanoparticle-Incorporated Calcium Silicate-Based Cement - Teena Sheethal Dsouza; Aditya Shetty; Neevan Dsouza (Bioinorganic Chemistry and Applications)
An experimental calcium silicate-based root-end filling material incorporated with silver nanoparticles intended for use in periapical surgeries was developed with the purpose to overcome the drawbacks of existing materials and to satisfy the ideal requirements of root-end filling materials. This study was designed to evaluate the physicochemical properties, pH, calcium ion release, and dimensional stability of the experimental cement, and compare the results with commercially available ProRoot MTA (Dentsply). An independent sample test was used to analyze the data. Mean initial pH (immediately after mixing) of the experimental cement was 10.42 ± 0.04 which was higher than that of MTA. However, there was a significant increase in pH of MTA at 1 day, 2 days, and 7 days. Presence of calcium chloride favored the release of calcium ions which was significantly increased in the experimental group at 24 hours. At the end of 30 days, MTA showed a significant expansion when compared to the experimental cement p<0.001. In conclusion, the experimental nanoparticle-incorporated calcium silicate-based cement showed clinically acceptable physicochemical properties.